Finding the Higgs boson through supersymmetry (2009)
ABSTRACT: The study of displaced vertices containing two b-jets may provide a double discovery at the Large Hadron Collider (LHC): we show how it may not only reveal evidence for supersymmetry, but also provide a way to uncover the Higgs boson necessary in the formulation of the electroweak theory in a large region of the parameter space. We quantify this explicitly using the simplest minimal supergravity model with bilinear breaking of R-parity, which accounts for the observed pattern of neutrino masses and mixings seen in neutrino oscillation experiments.